Transfer of Fiduciary Collateral Objects by Debtors Through Pawn without Creditor’s Consent: A Case Study of District Court Decision No. 1012/Pid.Sus/2024/PN TJK - Audyasari, Ruktanti; Harahap, Mhd Yadi (PALAR (Pakuan Law review), 2025)
Abstract  This study examines the practice of transferring fiduciary collateral objects by debtors through pawning without obtaining the creditor’s consent, with a particular focus on the District Court Decision of Tanjung Karang Number 1012/PID.SUS/2024/PN TJK. The increasing economic demands of society have encouraged the use of credit facilities from financing institutions, which commonly rely on fiduciary security as regulated under Law Number 42 of 1999. This instrument grants privileged rights to the fiduciary recipient. However, in practice, debtors frequently commit default by transferring the collateral object without the creditor’s written consent, thereby violating the provisions of Article 23 paragraph (2) of the Fiduciary Law. The purpose of this research is to analyze the legal provisions regarding the transfer of fiduciary collateral objects without creditor approval under Law Number 42 of 1999, as well as to examine the debtor’s legal liability in the case involving PT Adira Dinamika Finance Tbk. The research method employed is normative juridical, using statutory, case, and analytical approaches. Primary data sources consist of Law No. 42 of 1999 and the Indonesian Civil Code, supported by secondary data from academic literature and legal journals. The data were analyzed using a descriptive qualitative method. The findings indicate that the transfer of fiduciary collateral objects without written approval constitutes a criminal act, punishable by imprisonment of up to two years and a fine of Rp50,000,000, as stipulated in Article 36 of the Fiduciary Law. In the case of defendant Rio Aditia, it was proven that default and unlawful conduct occurred, resulting in financial losses for PT Adira Dinamika Multi Finance, Lampung Branch. Therefore, the creditor is entitled to claim compensation and execute the fiduciary collateral object based on the principle of droit de suite. Keywords: Fiduciary Collateral, Transfer of Objects, Creditor, Debtor